Զանգվածային լրատվամիջոցները ՀՀ պետական կառավարման համակարգում - Քալանթարյան, Էդգար (YSU Journal of International Affairs, 2015)
The recent reforms concerning activities of Media in the system of public administration of RA were marked by high efficiency. One of the most importantelements of public administration system in any country is the Media. At the same time, it is one of the most important institutions of the democratic system and civil society as it assumes the possibility of receiving and sending information. The Media are open and complicated structures that possess targeted adaptation as a result of changing realms, and self-government, with its self-regulative features. Thus, besides the clarification and enhancement of the Media’s public administration procedures, it will be possible to contribute in the state government efficiency of the RA, widening the civic rationality scale. Despite recent reforms, yet there are some problems of efficiency in the Media governing process in the public administration system of RA, especially in the legislative aspects, which is much more important for improving the governance.
Keywords: procedures for public administration of the mass media, legal status of the mass media, public administration, civil society, legislative reform, public institutions, effectiveness of state administration